Uso de simulações computacionais de evacuação e incêndio: um estudo de caso de uma edificação educacional - Volpatto, Janaína Saydelles (2023)
The safety of building users in fire situations is guaranteed by rapid evacuation and subsequent rapid firefighting. For evacuation to be successful, buildings must be equipped with appropriate conditions, such as unobstructed, accessible exit routes, with adequate signage and dimensioning. In this research, an educational building will be used as a case study, with the purpose of studying the impact of fire (Pyrosim software) during the evacuation of occupants (Pathfinder software). The building was modeled in BIM/Revit software and imported into simulation programs. The analysis of the passage widths of the exits available revealed that they exceed the requirements established by CBMRS Technical Resolution No. 11. Regarding the fire, considering the spread of smoke, temperature, visibility and concentration of CO, the parameter that came closest The tolerance limit was the CO concentration, since at 120 s it had already reached a critical limit, depending on the exposure time. The results were obtained regarding the evacuation time for the 3 proposed scenarios, for scenario 1 in a normal situation, with all exits and stairs available, and in scenarios 2 and 3 they were in a fire situation, whereas in scenario 2 they could only one of the stairs and 3 doors could be used, and in scenario 3 only one staircase and 2 doors could be used. In a normal situation, scenario 1, using the SFPE mode, had the shortest evacuation time, which was 88.8 s, and scenario 3, also using the same mode, but in a fire situation, had the longest evacuation time, which was 154.5 s. Graphs were generated where the total number of occupants at each exit were calculated, as well as the rate and flow and the specific flow in both simulated modes, for the 3 scenarios. The specific flow values in both Steering mode and SFPE mode did not reach the standard value for public meeting occupancy, which is 3.03 people/m.s, having reached the maximum specific flow in scenario 2 of 1.49 people/m.s. Given the results obtained, it was possible to conclude that through the combination of BIM technology, combined with Pyrosim and Pathfinder software, it provides a more detailed understanding of the influence of fire on the evacuation of the building and can allow the identification of possible improvements and optimizations in the process. in the design phase, enabling the development of projects that not only comply with standards, but are efficient and safe.